Recent Major Themes and Research Areas in the Study of Human-Environment Interaction in Prehistory. (2nd January 2020) - Carleton, W. Christopher; Collard, Mark
ABSTRACT: We report a study in which we systematically reviewed the recent literature dealing with human-environment interaction in prehistory. We first identified the 165 most highly cited papers published between 2005 and 2015. We then identified the major research themes covered in the sample of papers and assessed whether the themes fall into clusters and/or vary greatly in popularity. Subsequently, we identified potentially important lacunae. Our review identified dozens of themes and four major clusters: 1) improving our reconstructions of past environments; 2) the impact of climate change on past human societies; 3) human adaptation to past environmental conditions; and 4) human impacts on past environments. We also identified several gaps that led us to make a number of suggestions for future work. One is to pay more attention to the epistemology of causality. A second is to take into account nonlinearity when considering causal relationships. A third is to study the impact of chronological uncertainty on analyses. Lastly, our review revealed that there are differences between the aspects of human-environment interaction in prehistory that interest scholars and those that interest policy-makers and the general public. This needs to be addressed for obvious reasons.